Acute descending necrotizing mediastinitis as a complication of the retropharyngeal abscess caused by anaerobes (Journal of Health Sciences, 2020)
Descending necrotizing mediastinitis (DNM) is a rare, life-threatening form of mediastinitis caused by odontogenic, pharyngeal, or cervical infections. The retropharyngeal space is the most common primary site of infection. Given the fulminant course and high mortality rate, early diagnosis and prompt treatment are important predictors of survival in patients with DNM. Appropriate empirical antibiotic treatment, prompt surgical intervention, and proper management of patients in the intensive care unit can be of vital importance. We present the case of a previously healthy 20-year-old male patient who was successfully cured and discharged from the Clinical Center University of Sarajevo after suffering from a severe form of mediastinitis as a complication of the retropharyngeal abscess caused by anaerobes.